Environmental, Social and Governance (ESG) and Firm Investment Efficiency in Emerging Economy: A GMM Analysis - Muhammad Ali; Zavish Arshad; Khadija Tariq; Anam Ashraf; Uzair Ali (Indus Journal of Social Sciences, 2025)
Demands for more information outside the scope of conventional financial reporting, such as management conversations, governance data, and financial statement comments, have been sparked by significant changes in the corporate environment. Evidence shows that environmental, social, and governance (ESG) factors may increase investment efficiency, lower transaction costs, and win over stakeholders. To investigate the impact of ESG performance on investment efficiency, this research study undertakes step two system GMM analysis on a sample of Chinese A-share listed firms from 2013 to 2022. The Bloomberg database’s ESG score is used to gauge ESG performance. The findings demonstrate that investment efficiency is greatly increased by ESG performance. In addition to offering references for ESG practices and sustainable company growth in developing nations, this investigation adds to the body of literature on ESG performance.